2019
DOI: 10.1002/hyp.13597
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of baseflow nitrate loads by a recursive tracing source algorithm in a rainy agricultural watershed

Abstract: Baseflow has become an important source of nitrate nonpoint source pollution in many intensive agricultural watersheds. Uncertainties in baseflow nutrient load separation are caused by the effects of hydrometeorological factors on both baseflow recession and baseflow nutrient load recession. These uncertainties have not been addressed well in the existing separating algorithms, which are based on simple baseflow rate-load relationships. In the present study, a recursive tracing source algorithm (RTSA) was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Streamflow can be regarded as high‐frequency signals because of the influence of hydrological conditions caused by storm events. On the other hand, baseflow can be considered a low‐frequency signal because baseflow is relatively stable due to the storage effect of groundwater aquifers (He et al., 2020; He & Lu, 2016). Therefore, we adopted a two‐parameter low pass recursive digital filter (ECK filter) for baseflow separation proposed by Eckhardt (2005) to estimate daily baseflow from daily streamflow.…”
Section: Methodsmentioning
confidence: 99%
“…Streamflow can be regarded as high‐frequency signals because of the influence of hydrological conditions caused by storm events. On the other hand, baseflow can be considered a low‐frequency signal because baseflow is relatively stable due to the storage effect of groundwater aquifers (He et al., 2020; He & Lu, 2016). Therefore, we adopted a two‐parameter low pass recursive digital filter (ECK filter) for baseflow separation proposed by Eckhardt (2005) to estimate daily baseflow from daily streamflow.…”
Section: Methodsmentioning
confidence: 99%
“…Various reports have indicated that baseflow is one of the dominant hydrological pathways for NO 3 -N migration toward streams (He & Lu 2016). For example, the percentages of total NO 3 -N load contributed by baseflow were 66, 59, 52, and 62% for the Raccoon River watershed in the USA (Schilling & Zhang 2004), the Corberia watershed in Spain (Rodríguez-Blanco et al 2013), the Mulgrave River watershed in Australia (Rasiah et al 2013), and the Changle River watershed in China (He et al 2020), respectively. In the upper and middle HRB, the baseflow only accounted for one-fourth of the total natural runoff, while it contributed half of the total NPS NO 3 -N load.…”
Section: Preferential Hydrological Pathway Of No 3 -N Transportmentioning
confidence: 99%
“…Thanks to the availability of water quality databases belonging to numerous governmental organizations and the availability of various estimation methods (Aulenbach, 2013;Cohn, 2005;Cohn, Delong, Gilroy, Hirsch, & Wells, 1989;He, Hao, Wu, & Lu, 2020;Verhoff, Yaksich, & Melfi, 1980), the patterns of nitrate transport can be investigated. Even though the data held in these databases are usually collected in fixed sampling programs and so may be limited in their spatial and temporal resolution, these data can still support initial investigations of nitrate transport during consecutive dry years without requiring huge investments in time and resources (Sliva & Williams, 2001).…”
Section: Introductionmentioning
confidence: 99%